Perubahan bobot badan anak anjing lokal terinfeksi Toxocara canis setelah pemberian pyrantel pamoat di Kota Kupang - Didakdus W.N. Janis; Herlina U Deta; Aji Winarso (Jurnal Veteriner Nusantara, 2019)
Dog helmintiasis is generally caused by nematodes. The most destructive worm from nematode class is Toxocara canis. Toxocara canis causes worst thing for dog healthy. An adult worm infestation can cause less nutrition absorbtion in small intestine that leads to lose some weight. This research aims to have body weight gain in naturally infected local breed puppies by Toxocara canis after pyrantel pamoat administration in Kupang. Samples were taken from 24 domestic puppies at an early age of 1-2 month old which have positively infected by Toxocara canis. They were devided in to two groups. Groups 1: comprised of 20 puppies, they were feeding pyrantel pamoate on first day, the eight and the fifteen by the dose of 5 mg/kg weight on the contrary for the controlled groups there were four puppies. The parameter which had observed in this research were every egg per gram (EPG), weight gain (WG) and body condition scoring (BCS). The result showed that pyrantel pamoat medicine had good effect to eradicate worm infection of Toxocara canis. Pyrantel pamoate can reduce a number of worm eggs by the presentation FECRT of 97%, increasing puppy weight gain and puppy daily weight gain and also increasing body condition scoring of the puppies.